Investigation of Factors Influencing Voluntary Disclousure of Financial Information on The Internet by Indonesian Companies - Dody Hapsoro (The Indonesian Journal of Accounting Research, 2013)
The digital age has produced a dramatic shift in the corporate communication paradigm. As a result, companies increasingly use the internet (website) as an investor relations medium and a vehicle to disseminate financial information to capital markets. This paper investigates factors influencing voluntary disclosure of financial information on the internet by Indonesian companies. Cross-sectional analyses based on 50 companies listed on the Indonesia Stock Exchange in 2005 suggest that firm size and firm profitability are related with higher levels of voluntary financial information disclosure on corporate website.